PREDICTORS OF SOCIAL CARE NEEDS AND SELF-MANAGEMENT OF HIV IN OLDER AFRICAN-AMERICANS. (11th November 2018) - Hsueh, K; Klebert, M; Zimmerman, R; Cheng, W
Abstract: Self-management is essential for people living with chronic conditions including HIV. However, for older African-Americans OAAs (50 plus) living with HIV (one of the fastest growing, but understudied, disadvantaged groups) sustaining self-management is more difficult without supportive social care. Using data obtained from 65 HIV positive OAA patients of a university medical center, this study was to identify predictors of social care needs and self-management in OAAs living with HIV. We examined the associations among demographics, self-efficacy at HIV self-management, social care needs (demand for social services and social support), self-management behaviors (depression, and missed follow-up visits, and medication adherence), and self-management outcomes (effective immunity and HIV viral suppression). Results show that greater demand for social services was associated with lower levels of education (β = -.39); and greater demand for social support was associated with less education (β = -.29), living in poverty (β = .28), and being males (β = -.27). Lower levels of self-management self-efficacy were associated with depression (β = -.58), greater demand for social support (β = -.29), and more missed follow-up visits (β = -.25). The odds of missing follow-up visits increased by a factor of 8.71 for those living in poverty. The odds of maintaining HIV virus suppression decreased by a factor of 5.26 for those who had missed follow-up visits in the past 12 months. Findings add new information regarding predictors of social care and self-management among OAAs and provide directions for future development of effective HIV self-management programs for this population.